2013
DOI: 10.1167/iovs.12-10480
|View full text |Cite
|
Sign up to set email alerts
|

What Factors are Associated with Myopia in Young Adults? A Survey Study in Taiwan Military Conscripts

Abstract: PURPOSE. We investigated the independent impact of potential risk factors on myopia in young adults. METHODS.A survey study was conducted with male military conscripts aged 18 to 24 years between February 2010 and March 2011 in Taiwan. The participants were examined using non-cycloplegic autorefraction and biometry. The participants provided data about potential risk factors, including age, parental myopia, education, near work, outdoor activity, and urbanization. Myopia was defined as the mean spherical equiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
119
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(135 citation statements)
references
References 26 publications
11
119
0
5
Order By: Relevance
“…Table 4 gives a summary of studies examining the prevalence of myopia in young Asian and White men. [14][15][16][17][18] In particular, there were two studies on Korean male conscripts who were living in urban and rural environment. 15,16 The higher prevalence of myopia and high myopia in the urban population suggested that living environment may play a significant role in the development of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 gives a summary of studies examining the prevalence of myopia in young Asian and White men. [14][15][16][17][18] In particular, there were two studies on Korean male conscripts who were living in urban and rural environment. 15,16 The higher prevalence of myopia and high myopia in the urban population suggested that living environment may play a significant role in the development of myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Mutti et al (2002) initially reported that myopia prevalence was inversely related to time spent participating in sports. Several subsequent studies also have shown that outdoor activity is inversely related to the development of myopia (Dirani et al, 2009; Guo et al, 2013; Jones et al, 2007; Jones-Jordan et al, 2011; Lee et al, 2013; Onal et al, 2007; Rose et al, 2008a; Sherwin et al, 2012b; Wu et al, 2010). Some studies have reported that it is the time outdoors, independent of physical activity, that is the important variable (Guggenheim et al, 2012; Rose et al, 2008a).…”
Section: Human Studiesmentioning
confidence: 90%
“…[79] Although the cause of myopia is as yet unclear, genetic and environmental factors may contribute to its development. [1015] Some recent studies suggested that increasing time spent outdoors may prevent the development of myopia, [1417] although the results of some epidemiological studies oppose this theory. [18,19] …”
Section: Introductionmentioning
confidence: 99%